TINJAUAN HUKUM EKONOMI SYARIAH TERHADAP TRANSAKSI JUAL BELI DIAMOND MOBILE LEGEND PERSPEKTIF HUKUM POSITIF - Usman; Siska Yuliana (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2025)
This study aims to analyze the legal review of Islamic economics and the perspective of positive law related to diamond buying and selling transactions in the Mobile Legends Game. In the context of human needs for social media and the ease of online transactions, diamond buying and selling is an interesting phenomenon, but raises polemics regarding its permissibility according to Islamic law. This study examines the legal basis of Islamic law regarding buying and selling transactions, as well as fulfilling the requirements and pillars set out in Islam. Through a qualitative research method with a literature study approach, the results of the analysis show that this transaction is valid according to Islamic law, as long as it meets the appropriate criteria, including a clear contract and the object being traded has value and benefits. From a positive legal perspective, diamond buying and selling is regulated in the Civil Code and the ITE Law, which emphasize the importance of transparency and good faith in electronic transactions. This study recommends the need for clear regulations and effective law enforcement to protect consumers and maintain the integrity of transactions in cyberspace. Keywords: Syari’ah Ekonomic Law, Buying and Selling Transactions, Positive Law